ACTIVITY BASED COSTING SYSTEM DALAM PENENTUAN HARGA POKOK KAMAR HOTEL PONDOK ASRI - ARIFIANTO, TEGUH; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
In the modern era with tight competition, cost distortion will occur when the calculation of room baseprice is not exactly right. It has made the management party requires more accurate method in determiningroom base price. This method is Activity Based Costing since this method charges cost based on the activities soits accuracy level is better. This research has been conducted at Hotel Pondok Asri and qualitative research withdescriptive approach and 2014 company data. The data collection has been carried out in three stages: first stage,direct observation is conducted directly to the room service activities; second stage, conduct interview to themanager about the hotel services and third stage, conduct documentation by recording and data collecting andthe amount of cost. Based on the result of the analysis about the comparison of the calculation of traditionalmethod room base price and Activity Based Costing for room types i.e. Standard A, Standard B, Standard C andFamily Room when it is done by using Activity Based Costing, the room base price is low. Meanwhile, the roomtype i.e. Penthouse indicates high cost of room base price. Activities in Activity Based Costing System becomesthe point of cost accumulation i.e. costs are traced to activities and these activities are traced to products whichare based on the use of products.Keywords: Room base price, activity based costing, activities